Immunogenicity, Safety and Antibody Persistence of a Booster Dose of Quadrivalent Meningococcal ACWY-tetanus Toxoid Conjugate Vaccine Compared with Monovalent Meningococcal Serogroup C Vaccine Administered Four Years After Primary Vaccination Using the Same Vaccines. Issue 12 (December 2015) - Vesikari, Timo; Forsten, Aino; Bianco, Veronique; Van der Wielen, Marie; Miller, Jacqueline M.
Abstract : Background: We evaluated safety, immunogenicity and antibody persistence of meningococcal serogroups A, C, W and Y tetanus toxoid conjugate vaccine (MenACWY-TT) booster vaccination 4 years after priming of toddlers. Methods: This phase III, open-label, controlled study in Finland (NCT00955682) enrolled children previously randomized (3:1) at 12–23 months (NCT00474266) to receive 1 dose of MenACWY-TT or MenC conjugate vaccine (MenC-CRM197 ). Serum bactericidal antibody titers using rabbit (rSBA, cut-off 1:8) and human complement (hSBA, cut-off 1:8) were assessed at year 3 and 4 after priming and 1 month and 1 year after administration of a booster dose of the same vaccine given for primary vaccination. Reactogenicity and safety were assessed, and vaccination-related serious adverse events were recorded from the time of primary vaccination. Results: Before booster (year 4), 74.1%, 40.4%, 49.3% and 58.2% of MenACWY-TT-recipients retained rSBA titers ≥1:8 for serogroups A, C, W and Y, respectively; 28.8%, 73.2%, 80.6% and 65.4% retained hSBA ≥1:8. Percentages for the MenC-CRM group were 35.6% (rSBA-MenC) and 46.9% (hSBA-MenC). After MenACWY-TT booster, ≥99.5% had rSBA ≥1:8 and hSBA ≥1:8 for each serogroup. After MenC-CRM197 booster, all children had rSBA-MenC ≥1:8 and hSBA-MenC ≥1:8. At year 5, percentages above the cut-off were ≥97.4% (rSBA) and ≥95.5% (hSBA) in MenACWY-TT-vaccinees for each serogroup. The MenACWY-TT booster dose had a clinically acceptable safety profile. No vaccine-related serious adverse events were reported. Conclusion: There was evidence of antibody persistence 4 years after toddlers were primed with MenACWY-TT. Booster vaccination induced robust immune responses for all serogroups with an acceptable safety profile. Abstract : Supplemental Digital Content is available in the text.